Implementasi Prinsip-prinsip Kewarganegaraan dalam Pembentukan Perundang-undangan: Studi Kasus Hukum Islam: The Implementation of Citizenship Principles in Legislation: A Case Study of Islamic Law - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Muhammad Ainun Najib; Saad Prasetyo; Evrilliana Aghniya Qolbinanisa (Litera Academica Publishing, 2025)
This research examines the implementation of citizenship principles in the formulation of legislation based on Islamic law, focusing on the dynamics and challenges faced in various Muslim-majority countries. Through a comparative analysis of several countries such as Saudi Arabia, Iran, Indonesia, and Malaysia, this study finds that approaches to integrating Islamic law and citizenship vary greatly, depending on the historical, cultural, and political context of each nation. Countries like Saudi Arabia and Iran strictly apply Islamic law as the foundation of their legal systems, often at the expense of modern citizenship principles. In contrast, Indonesia and Malaysia attempt to accommodate Islamic law within a more inclusive national legal framework, although not without controversy and challenges. This research also demonstrates that the successful integration of Islamic law and citizenship principles largely depends on the ability of governments and societies to engage in dialogue and negotiation, as well as on the flexibility of Islamic legal interpretation to respond to the demands of the modern era.